Ischemic Conditioning in Kidney Transplantation. (July 2017) - Veighey, Kristin; MacAllister, Raymond
Ischemia–reperfusion injury is a composite of the injury sustained during a period of reduced or absent blood flow to a tissue or organ and the additional insult sustained on reperfusion, which limits the amount of tissue that can be salvaged. Ischemia–reperfusion injury is the predominant insult during kidney transplantation, contributing to graft dysfunction, increased rates of acute rejection, and reduced rejection-free graft survival. In this review, we discuss the potential therapeutic benefits of a cost-effective and low-risk intervention, ischemic preconditioning, and its potential for improving kidney function following transplantation.